Shear Wave Elastography for measuring the elastic properties of the Psoas Major muscle: An intra- and inter-examiner reliability study - Gabriel Rabanal-Rodríguez; César Fernández-de-las-Peñas; Javier Álvarez-González; Alberto Roldán-Ruiz; Jorge Buffet-García; Juan Antonio Valera-Calero (PLoS ONE, 2025)
Background The psoas major (PM) plays an important role in population with low back pain (LBP). Its evaluation considers clinical history, which can be confused with other lumbar and lower limb conditions, physical examination, with an inconsistent palpation, and imaging tests that provide inconclusive parameters in various studies. Therefore, developing reliable assessment procedures to evaluate PM elastic properties is necessary to improve diagnosis and follow-up. This study aimed to evaluate the intra and inter-examiner reliability of shear wave elastography (SWE) for calculating the PM stiffness in patients with LBP. Design Observational study. Methods Longitudinal views of the of the PM muscle using SWE were acquired bilaterally in 52 volunteers experiencing moderate LBP and disability. All measurements were performed twice, involving the assessment of shear wave speed and Young’s modulus as indicators of stiffness, with data collected by an experienced examiner and a novice examiner. Results Test-retest reliability showed strong consistency regardless of the examiner’s level of experience, with intraclass correlation coefficients (ICCs) exceeding 0.9 for both metrics. However, experienced examiners achieved smaller minimal detectable changes. Inter-examiner reliability was comparatively lower, with ICCs ranging from 0.854 to 0.925, and notable differences in mean values between examiners were observed (p < 0.01). Conclusion Excellent test-retest reliability was observed for the measurement of PM muscle stiffness in chronic LBP patients using SWE by both experienced and novice evaluators, although statistically significant differences were found between the two trials for the novice examiner. Inter-examiner reliability was lower, highlighting variability between assessors. To minimize errors and improve consistency and accuracy, if multiple examiners are involved, averaging measurements is recommended.